Using games as interactive learning tools in accounting courses / Noor Hasimah M Yacob …[et al.] - M Yacob, Noor Hasimah; Md Zeni, Syahida; Azis, Saflina; Mat, Mustafa Kamal (2016)
Accounting courses have always been perceived as dry and difficult to understand. In order to attract students to love accounting, educators try to find interactive tools in teaching the students. Many researchers have carried out studies on interactive learning tools that can be used in teaching accounting subject. This paper reviews the literature of using games as interactive learning tools in accounting courses. The aim of this paper is to explore the types of games used in learning accounting courses. It also highlights the strength and weaknesses of the games used. In order to achieve the research objectives several games used by previous researchers are discussed in this study namely; Financial Statement Bingo, Double Entry Monopoly Games and Crossword Puzzle. Most of the literature highlighted that these interactive learning tools will make learning more fun and easier to understand, promote teamwork and stimulate the ability to think among the students. However, several weaknesses were discovered such as time constraint and it will burden the educators in terms of preparing the games and getting familiar with the rules of the games. Nevertheless, considering all the benefits of the games used, educators should try to apply these games in teaching accounting courses.